Association among age, gender, menopausal status and small dense low-density lipoprotein cholesterol: a cross-sectional study - Shizukiyo Ishikawa; Yosikazu Nakamura; Yukihiro Sato; Toshihide Izumida (BMJ Open)
Objectives Small dense low-density lipoprotein cholesterol (sdLDL-C) might be a better cardiovascular disease (CVD) indicator than low-density lipoprotein cholesterol (LDL-C); however, details regarding its epidemiology remain elusive. The present study aimed at evaluating the association between the demographic factors, such as age, gender and menopausal status, and sdLDL-C levels and sdLDL-C/LDL-C ratio in the Japanese population.Design This was a cross-sectional study.Setting 13 rural districts in Japan, 2010–2017.Participants This study included 5208 participants (2397 men and 2811 women), who underwent the health mass screening that was conducted in accordance with the medical care system for the elderly and obtained informed consent for this study.Results In total, 517 premenopausal women (mean age ±SD, 45.1±4.2 years), 2294 postmenopausal women (66.5±8.8 years) and 2397 men (64.1±11.2 years) were analysed. In men, the sdLDL-C levels and sdLDL-C/LDL-C ratio increased during younger adulthood, peaked (36.4 mg/dL, 0.35) at 50–54 years, and then decreased. In women, relatively regular increasing trends of sdLDL-C level and sdLDL-C/LDL-C ratio until approximately 65 years (32.7 mg/dL, 0.28), followed by a downward or pleated trend. Given the beta value of age, body mass index, fasting glucose and smoking and drinking status by multiple linear regression analysis, standardised sdLDL-C levels and sdLDL-C/LDL-C ratio in 50-year-old men, premenopausal women and postmenopausal women were 26.6, 22.7 and 27.4 mg/dL and 0.24, 0.15 and 0.23, respectively. The differences between premenopausal and postmenopausal women were significant (p<0.001).Conclusions SdLDL-C and sdLDL-C/LDL-C ratios showed different distributions by age, gender and menopausal status. A subgroup-specific approach would be necessary to implement sdLDL-C for CVD prevention strategies, fully considering age-related trends, gender differences and menopausal status.